The determinants of dividend policy on Chinese high-tech firms - Ma, Lie (2016)
The purpose of this study is to investigate the relationship between dividend payout ratio in Chinese High-tech firms with profitability, firm size, growth opportunities, leverage and liquidity. The study used a sample of 226 firms listed on the Shenzhen stock exchange and Shanghai stock exchange. These firms were taken from high technology industry sector in China. In order to explain the relationships as stated above, ordinary least squares regression analysis is used to test the hypotheses. The study found that at the pooled data level for whole study period, profitability, growth opportunity, liquidity and firm size have significant positive correlation with dividend payout ratio(DPR). The variable leverage, however, has a strong negative correlation with dividend payout ratio. The findings however differ from term to term (short term, medium term and long term); results reflect that leverage is the common variables which have influence on DPR across various terms, where profitability, growth opportunity, liquidity and firm size are not significantly associated with DPR in short term (0-3 years). Similarly, profitability, liquidity and growth opportunity have no influence on the dividend payout ratio of the companies in the medium term (4-7 years). All variables have significant influence on DPR except growth opportunity.